Amidu. 2007. Semantic Assignment Rules in Bantu Classes: Amidu. 2007. Semantic Assignment Rules in Bantu Classes - Dingemanse, Mark (AAeO - Afrikanistik-Aegyptologie-Online, 2008)
Assibi A. Amidu. 2007. Semantic Assignment Rules in Bantu Classes. A Reanalysis Based on Kiswahili. East African Languages and Dialects 18. XIV, 138 pp., numerous tables and overviews. € 29,80. ISBN 978-3-89645-703-5